1986
DOI: 10.1088/0034-4885/49/8/001
|View full text |Cite
|
Sign up to set email alerts
|

Baryons in the Skyrme model

Abstract: The ideas underlying the Skyrme model for baryons are introduced. Applications for the properties of single baryons ( B = 1) in the case of two and three flavours are based on Skyrme's hedgehog ansatz. The interaction between two baryons is discussed within the product ansatz for the B = 2 system. The pion baryon S matrix is derived in the adiabatic approximation. The possibility to include quark degrees of freedom is shown in terms of the hybrid model. Finally the origin and implications of the Wess-Zumino-Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 69 publications
3
105
0
Order By: Relevance
“…The major focus of these three flavor soliton models is on the description of the low-lying J π = 1 2 + and 3 2 + baryons. These objects of interest are displayed in figure 1.1 in form of the popular representations of flavor SU (3). The baryons p, n, .…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…The major focus of these three flavor soliton models is on the description of the low-lying J π = 1 2 + and 3 2 + baryons. These objects of interest are displayed in figure 1.1 in form of the popular representations of flavor SU (3). The baryons p, n, .…”
Section: 1mentioning
confidence: 99%
“…The ellipsis in eq (2.57) represent terms, which vanish when sandwiched between baryon states. According to the quantization prescription (2.34) the angular velocities Ω a are substituted by the right generators R a of SU (3). Taking the Fourier transform of the resulting matrix elements allows one to identify the magnetic form factor in the Breit frame [69,70] …”
Section: )mentioning
confidence: 99%
“…Its connection to phenomenological nuclear forces is well established (Nyman & Riska 1990), and its justification based on large N c arguments ('t Hooft 1974) stemming from a quark-gluon picture indicates that it acts as a ''bridge'' between QCD and nucleonnucleon (n-n) forces. Several detailed reviews on the Skyrme model may be found in the literature (Holzwarth & Schwesinger 1986;Zahed & Brown 1986;Schechter & Weigel 1999).…”
Section: The Skyrme Modelmentioning
confidence: 99%
“…These quantities are simply related [3,4,5] to the proton and neutron electric and magnetic radii < r 2 E,M > p,n and respective magnetic moments µ p,n . We also include the axialvector coupling constant g A .…”
Section: Our Analysismentioning
confidence: 99%
“…General reviews of the Skyrme model have been written by Holzwarth and Schwesinger [3], Zahed and Brown [4] and Meissner [5], among others.…”
Section: Introductionmentioning
confidence: 99%